2014
DOI: 10.1177/0748233714560394
|View full text |Cite
|
Sign up to set email alerts
|

Co-treatment of chlorpyrifos and lead induce serum lipid disorders in rats

Abstract: The aim of this study was to investigate the effects of taurine (TA) on serum lipid profiles following chronic coadministration of chlorpyrifos (CP) and lead acetate (Pb) in male Wistar rats. Fifty rats randomly distributed into five groups served as subjects. Distilled water (DW) was given to DW group, while soya oil (SO; 1 mL kg(-1)) was given to SO group. The TA group was treated with TA (50 mg kg(-1)). The CP + Pb group was administered sequentially with CP (4.25 mg kg(-1); 1/20th median lethal dose (LD50)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…Our data was in accordance with some authors who studied the protective effect of TA on embryotoxicity. [ 14–43 ] A recent study demonstrated a positive correlation between maternal TA intake and fetal length in human subjects. [ 44 ] Although we did not observe a significant change between fetuses of TA‐supplemented dams and the control ones, TA pretreatment significantly increased fetal length of the Pb‐treated group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data was in accordance with some authors who studied the protective effect of TA on embryotoxicity. [ 14–43 ] A recent study demonstrated a positive correlation between maternal TA intake and fetal length in human subjects. [ 44 ] Although we did not observe a significant change between fetuses of TA‐supplemented dams and the control ones, TA pretreatment significantly increased fetal length of the Pb‐treated group.…”
Section: Discussionmentioning
confidence: 99%
“…This dose has been previously shown to be effective to mitigate cognitive impairment, lipid peroxidation, and antioxidants depletion induced by lead acetate and chlorpyrifos in male rats. [ 23 ]…”
Section: Methodsmentioning
confidence: 99%
“…It is known that TA may impede lipid peroxidation by increasing the activities of GPx and SOD in biological systems [30] . It has been postulated that TA decreased serum MDA concentration in male Wistar rats co-administered with chlorpyrifos and lead probably through its antioxidant properties [18] . To the best of our knowledge, this is the first investigation in which TA was reported to mitigate subacute DP toxicity through the alleviation of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the activities of the serum antioxidant enzymes were augmented in the rats that were treated with TA. It has been demonstrated that TA enhanced the activities of serum antioxidant enzymes in male Wistar rats exposed to environmental toxicants [18] . According to Eppler and Dawson [34] , TA elicits its antioxidant effects by improvement of the antioxidant system, production of chloramines with hypochlorous acid and restoration of GSH during oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation